The Implementation of the Project Based Learning Model based on GRASPS in Fostering Students Creativity at SMP Negeri 3 Gunung Jati - Nurcholish, Muhammad Olish; Abidin, Zaenal; Arip, Asep Ginanjar (Peneliti.net, 2024)
This research aims to examine the feasibility of implementing the Project Based Learning (PBL) model based on Goal, Role, Audience, Situation, Product, and Standard (GRASPS) in fostering naturalistic intelligence and creativity among 7th-grade students at SMP Negeri 3 Gunung Jati. The research was conducted at SMP Negeri 3 Gunung Jati from October to December 2022. The research was carried out using an experimental method with a Non-Equivalent Control Group Design. The variable in this research is creativity. The research population consisted of 124 students. The research sample included 21 students from class VII C and 21 students from class VII D. The researcher used cluster sampling technique for sampling. The data collection instruments used were rubrics and student response questionnaires. Based on the results of the research conducted on